Impact of Chirality on the Dynamic Susceptibility of Concentric Nanotori - Saavedra-Díaz, E (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
This study investigates the influence of chirality on the dynamic susceptibility of concentric nanotori via micromagnetic simulations. The aim is to analyze the ferromagnetic resonance characteristics of coupled nanotori structures and compare them across various ring separation distances, thus providing an insight into how vortex configurations with identical or differing chiralities affect their dynamic properties. We analyze the energetic differences between the two vortex configurations and find them to be negligible; however, these minor differences suffice to explain the significant discrepancies in the demagnetization field observed between the nanotori. We examine the dynamic susceptibility spectrum and the spatial localization of the ferromagnetic resonance modes for different nanotori separations. Our findings demonstrate that the resonant oscillation frequencies are significantly influenced by the magnetostatic interactions between the nanotori, which can be effectively modulated by varying the distance between them. Furthermore, for smaller separations, the frequency peaks in the dynamic susceptibility markedly diverge between the two vortex configurations, demonstrating that the observed differences in the demagnetization field between the rings strongly influence the frequency response. In summary, our results indicate that both the inter-ring distance and the vortex configuration play a crucial role in determining the frequency response of the system.